2004
DOI: 10.1002/uog.1035
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic demonstration of brain injury in fetuses with severe red blood cell alloimmunization undergoing intrauterine transfusions

Abstract: K E Y W O R D S:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…Ghi et al reported on prenatal diagnosis of brain injury in four out of seven fetuses with severe anemia caused by RBC alloimmunization; three of them were transfused before 22 weeks of gestation. In all four fetuses, the Hb level at the time of the first transfusion was < 20 g/L, and two fetuses were found to have a cerebellar hemorrhage similar to our case 25 . In the two cases reported by Ghi et al, as well as in ours, the cerebellar abnormalities were seen only after the first transfusion.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Ghi et al reported on prenatal diagnosis of brain injury in four out of seven fetuses with severe anemia caused by RBC alloimmunization; three of them were transfused before 22 weeks of gestation. In all four fetuses, the Hb level at the time of the first transfusion was < 20 g/L, and two fetuses were found to have a cerebellar hemorrhage similar to our case 25 . In the two cases reported by Ghi et al, as well as in ours, the cerebellar abnormalities were seen only after the first transfusion.…”
Section: Discussionsupporting
confidence: 77%
“…The baseline characteristics of these women are summarized in Table 1. Ten women were noted to have had at least one previous stillbirth as a result of alloimmunization at a median gestational age of 24 weeks (range, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Of this cohort, 26 (87%) were associated with anti-D, four (13%) with anti-Kell and 12 had more than one antibody type involved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Hydropic fetuses due to anaemia by red-blood-cell alloimmunization (seven fetuses with mean gestational age of 22 AE 2.5 weeks) underwent multiplanar brain sonography. 18 Abnormalities were found in four: two intracerebellar haemorrhages after the first transfusion, one severe brain oedema before transfusion which later developed cystic PVL, and one unilateral ventriculomegaly after the first transfusion which disappeared. Postmortem neuropathological examination of children with hydrops fetalis revealed cerebral abnormalities originating from the intrauterine period: microcalcifications, cerebral and/or cerebellar hypoplasia, microcephaly, encephalomalacia, cavitary lesions, astrocytosis, polymicrogyria, and severe neuronal loss.…”
Section: Age-related Predilection Areasmentioning
confidence: 98%
“…Also, some cerebral lesions are not due to defective embryological development but represent the consequence of acquired prenatal or perinatal damage. [44][45][46] The most important congenital anomalies of the nervous system concerning prevalence and severity are usually detectable during the FT scan, including holoproencephaly and some neural tube defects (NTDs). The visualization of the falx cerebri, calvaria and head shape are easily achieved in the FT transverse incidence, thus, holoprosencephaly and encephalocele are detectable.…”
Section: The First Trimester Central Nervous System Morphological Assmentioning
confidence: 99%